Controlled meteorological (CMET) balloon profiling of the Arctic atmospheric boundary layer around Spitsbergen compared to a mesoscale model - Roberts, Tjarda; Voss, P. B.; Dütsch, M.; Hole, L. R. (HAL CCSD, 2015)
International audience Observations from CMET (Controlled Meteorological) balloons are analyzed in combination with mesoscale model simulations to provide insights into tropospheric meteorological conditions (temperature, humidity, wind-speed) around Svalbard, European High Arctic. Five Controlled Meteorological (CMET) balloons were launched from Ny-Ålesund in Svalbard over 5-12 May 2011, and measured vertical atmospheric profiles above Spitsbergen Island and over coastal areas to both the east and west. One notable CMET flight achieved a suite of 18 continuous soundings that probed the Arctic marine boundary layer over a period of more than 10 h. The CMET profiles are compared to simulations using the Weather Research and Forecasting (WRF) model using nested grids and three different boundary layer schemes. Variability between the three model schemes was typically smaller than the discrepancies between the model runs and the observations. Over Spitsbergen, the CMET flights identified temperature inversions and low-level jets (LLJ) that were not captured by the model. Nevertheless, the model largely reproduced time-series obtained from the Ny-Ålesund meteorological station, with exception of surface winds during the LLJ. Over sea-ice east of Svalbard the model underestimated potential temperature and overestimated wind-speed compared to the CMET observations. This is most likely due to the full sea-ice coverage assumed by the model, and consequent underestimation of ocean-atmosphere exchange in the presence of leads or fractional coverage. The suite of continuous CMET soundings over a sea-ice free region to the northwest of Svalbard are analysed spatially and temporally, and compared to the model. The observed along-flight daytime increase in relative humidity is interpreted in terms of the diurnal cycle, and in the context of marine and terrestrial air-mass influences. Analysis of the balloon trajectory during the CMET soundings identifies strong wind-shear, with a low-level channeled flow. The study ...